Cognitive Function in Heart Failure Is Associated With Nonsomatic Symptoms of Depression But Not Somatic Symptoms. Issue 5 (September 2015) - Hawkins, Misty A.W.; Dolansky, Mary A.; Schaefer, Julie T.; Fulcher, Michael J.; Gunstad, John; Redle, Joseph D.; Josephson, Richard; Hughes, Joel W.
Abstract : Background: Patients with heart failure (HF) have high rates of cognitive impairment and depressive symptoms. Depressive symptoms have been associated with greater cognitive impairments in HF; however, it is not known whether particular clusters of depressive symptoms are more detrimental to cognition than others. Objective: The aim of this study was to identify whether somatic and/or nonsomatic depressive symptom clusters were associated with cognitive function in persons with HF. Methods: Participants were 326 HF patients (40.5% women, 26.7% non-white race-ethnicity, aged 68.6 ± 9.7 years). Depressive symptoms were measured using a depression questionnaire commonly used in medical populations: the Patient Health Questionnaire-9. Somatic and nonsomatic subscale scores were created using previous factor analytic results. A neuropsychological battery tested attention, executive function, and memory. Composites were created using averages of age-adjusted scaled scores. Regressions adjusting for demographic and clinical factors were conducted. Results: Regressions revealed that Patient Health Questionnaire-9 total was associated with attention ( β = −.14, P = .008) and executive function ( β = −.17, P = .001). When analyzed separately, the nonsomatic subscale, but not the somatic symptoms subscale ( P values ≥ .092), was associated with attention scores ( β = −.15, P = .004) and memory ( β = −.11, P = .044). Both nonsomatic ( β = −.18, P < .001) and somatic ( β = −.11, P = .048) symptoms were related to executive function. When included together, only the nonsomatic symptom cluster was associated with attention ( β = −.15, P = .020) and executive function ( β = −.19, P = .003). Conclusions: Greater overall depressive symptom severity was associated with poorer performance on multiple cognitive domains, an effect driven primarily by the nonsomatic symptoms of depression. Clinical Implications: These findings suggest that screening explicitly for nonsomatic depressive symptoms may be warranted and that the mechanisms underlying the depression-cognitive function relationship in HF are not solely related to sleep or appetite disturbance. Thus, interventions that target patients' somatic symptoms only (eg, poor appetite or fatigue) may not yield maximum cognitive benefit compared with a comprehensive treatment that targets depressed mood, anhedonia, and other nonsomatic symptoms.